Regulation of private health care providers in India: current status, future directions - Chakravarthi, Indira (2018)
In the current context of more expansive role for private sector in health systems, especially in universal health coverage (UHC), its regulation has gained importance in health policy discourse. This article provides an overview of the existing regulatory mechanisms and their implementation in India, the enormity of the regulatory challenges raised by the nature of the private health care sector here and the available alternatives. - Reproduced.
Keywords: Administrative agencies; Regulation; Health services - Regulation - India